2011
DOI: 10.1108/03074351111113333
|View full text |Cite
|
Sign up to set email alerts
|

The stock market reaction to stock dividends in Nigeria and their information content

Abstract: Purpose -To examine whether stock dividend announcements create value for companies traded on the Nigerian stock market and to ascertain the nature of the information such announcements convey.Design/methodology/approach -A standard event study methodology, employing the market model, is applied to determine the abnormal returns both on and surrounding the stock dividend announcement date. Our sample is broken down based on the timing of announcements and on the frequency with which the announcing companies' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
(93 reference statements)
2
17
0
3
Order By: Relevance
“…Consistent with the above studies, a similar study conducted by Campbell and Ohuocha (2011) Market. In addition, based on the results and considering the characteristics of the market, they suggest that these abnormalities may be due to information leakage than the market's prior anticipation.…”
Section: (Ii) Nigeriasupporting
confidence: 85%
See 3 more Smart Citations
“…Consistent with the above studies, a similar study conducted by Campbell and Ohuocha (2011) Market. In addition, based on the results and considering the characteristics of the market, they suggest that these abnormalities may be due to information leakage than the market's prior anticipation.…”
Section: (Ii) Nigeriasupporting
confidence: 85%
“…It is important to note that the findings of this study are consistent with many of the similar empirical studies on other emerging stock markets. Similar to studies of Dhar and Chhaochharja (2008) on the Indian Stock Market, Barnes and Ma (2002) on the China's Stock Market, Olowe (1998) and Campbell and Ohuocha (2011) on the Nigerian Stock Market, Akbar and Baig (2010) on the Karachi Stock Exchange, it is found that stock prices respond positively to bonus share issue announcements. Further, consistent with the studies conducted by Olowe (1998), Akbar and Baig (2010), and Campbell and Ohuocha (2011), the findings of this study suggest that CSE is not efficient in its semi-strong form.…”
Section: Comparison With Similar Studies On Other Emerging Stock Marketssupporting
confidence: 78%
See 2 more Smart Citations
“…Normal trading range hypothesis yang diajukan Ikenberry et al (1996) beranggapan bahwa perusahaan mengeluarkan saham bonus dengan harapan harga sahamnya akan turun di harga perdagangan yang optimal. Dan yang teori paling terkenal dalam menjelaskan motif saham bonus adalah signalling theory, dimana manajer perusahaan berusaha untuk mengurangi asymmetric information mengenai prospek perusahaan di masa mendatang dengan melakukan pembagian saham bonus seperti yang dijelaskan Grinblatt et al (1984) dan McNichols & Dravid (1990) dalam Campbell & Ohuocha (2011).…”
Section: Pendahuluanunclassified